Gambaran Implementasi Manajemen Kesehatan dan Keselamatan Kerja pada Tenaga Medis dan Non Medis Rumah Sakit X - Nathaniela Kezia Hermawan; Lilik Sriwiyati; I Putu Juni Andika; Sri Aminingsih (CV Edujavare Publishing, 2026)
Hospitals are work environments with high levels of occupational safety and health risks for medical and non-medical personnel, requiring the implementation of Hospital Occupational Health and Safety (K3RS) management through the application of risk management and preparedness in dealing with emergency situations.This study used a descriptive quantitative design with a cross-sectional approach.The research subjects consisted of 120 respondents, including medical and non-medical personnel, who were selected using purposive sampling. Data were collected using questionnaires and analyzed univariately. The implementation of risk management was mostly in the good category, although there were still obstacles in the consistency of incident reporting and the application of ergonomic principles in the work environment. The level of preparedness of medical and non-medical personnel was also mostly in the good category, as indicated by their understanding of hazard reporting mechanisms, risk documentation, and emergency response procedures. Respondent characteristics such as length of service and education level also influenced the implementation of K3RS. The implementation of risk management and preparedness has been good, but still needs improvement through strengthening the reporting culture, continuous monitoring, and improving workplace ergonomics.